Chinese contract law : civil and common law perspectives / edited by Larry A. Dimatteo, University of Florida, Lei Chen, City University of Hong Kong. - DiMatteo, Larry A.; Chen, Lei (Lawyer) (Cambridge University Press, 2018)
This book is the product of a unique collaboration between Mainland Chinese scholars and scholars from the civil, common, and mixed jurisdiction legal traditions. It begins by placing the current Chinese Contract Law (CCL) in the context of an evolutionary process accelerated during China's transition to a market economy. It is structured around the core areas of contract law, anticipatory repudiation (common law) and defense of security (German law); and remedies and damages, with a focus on the availability of specific performance in Chinese law. The book also offers a useful comparison between the CCL and the UNIDROIT Principles of International Commercial Contracts, as well as the Convention on Contracts for the International Sale of Goods. The analysis in the book is undertaken at two levels - practical application of the CCL and scholarly commentary.